2006
DOI: 10.1143/jjap.45.l339
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical Approach to Analysis of Ferroelectric Transition in BaxSr1-xTiO3 Epitaxial Films

Abstract: When Sr1-xBaxTiO3 (0 Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…This is not consistent with the observations, and therefore we conclude that the change is band gap is not a dominant factor in determining the composition dependence of the reactivity. However, it should also be mentioned that the composition dependence of the photochemical reduction of silver in nanostructured Ba 1− x Sr x TiO 3 thin films, which do not exhibit band bending, was explained by changes in the band gap 27 . For that case, both the composition dependence of the reactivity and the band gaps differed substantially from the bulk material described here 27 …”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations
“…This is not consistent with the observations, and therefore we conclude that the change is band gap is not a dominant factor in determining the composition dependence of the reactivity. However, it should also be mentioned that the composition dependence of the photochemical reduction of silver in nanostructured Ba 1− x Sr x TiO 3 thin films, which do not exhibit band bending, was explained by changes in the band gap 27 . For that case, both the composition dependence of the reactivity and the band gaps differed substantially from the bulk material described here 27 …”
Section: Discussionmentioning
confidence: 65%
“…However, it should also be mentioned that the composition dependence of the photochemical reduction of silver in nanostructured Ba 1Àx Sr x TiO 3 thin films, which do not exhibit band bending, was explained by changes in the band gap. 27 For that case, both the composition dependence of the reactivity and the band gaps differed substantially from the bulk material described here. 27 Polarization within the domains changes dramatically as a function of composition and this also has the potential to affect the reactivity.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…Samantaray et al 42 also reported a similar smooth increase with strontium content from 3.25 eV to 3.55 eV. Ohara et al 43 reported that the band gap initially decreases with increasing strontium content (from 0 < x < 0.4), including an abrupt 125 mV step change at the cubic to-tetragonal transition. The grain size, film thickness, and lattice strain can all influence the observed band gaps in these films and this is likely to account for the inconsistency of the reports.…”
Section: Discussionmentioning
confidence: 82%